RELATION OF HYPERTENSION WITH BODY MASS INDEX AND AGE IN MALE AND FEMALE POPULATION OF PESHAWAR, PAKISTAN - Humayun, Anjum; Shah, Arbab Sher; Sultana, Riffat (Journal of Ayub Medical College Abbottabad, 2009)
Background: Hypertension, a condition developed as a result of high blood pressure is strongly correlated with body mass index (BMI). Obesity was noted to be a single best predictor of hypertension incidence, and was regarded as a major controllable contributor to hypertension. Overweight and obesity is conveniently determined from BMI. Present study was conducted in Khyber Medical College (KMC) Peshawar to investigate the relation of hypertension with BMI and age. The objective of the present investigation is to establish a relationship between hypertension and BMI in male and female population of Peshawar with consideration of age. Methods: This study was conducted at KMC, Peshawar during 2008-2009. A total of 1006 adult male and female volunteers were the subject of present research and were categorised in terms of their ages. BMI was determined from weight and height; the subjects were grouped as normal, overweight and obese. Hypertension was determined from the measure of blood pressure. Results: The results show a consistence relation between BMI and hypertension within age groups in both male and females. The figures exhibited a relation of age with BMI and hypertension in both males and females subjects. Conclusion: The results showed a higher trend of hypertension with increasing BMI. In young females it was noted that with a shift from normal BMI the incidence of hypertension was very high. Keywords: Hypertension, BMI, blood pressure